2021
DOI: 10.3389/fpsyt.2021.658967
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Training in Psychiatry for Medical Education: A Review

Abstract: Despite recognised benefits of Simulation-Based Education (SBE) in healthcare, specific adaptations required within psychiatry have slowed its adoption. This article aims to discuss conceptual and practical features of SBE in psychiatry that may support or limit its development, so as to encourage clinicians and educators to consider the implementation of SBE in their practice. SBE took off with the aviation industry and has been steadily adopted in clinical education, alongside role play and patient educators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Human simulation has had a limited, but far from trivial role in psychiatric education and training[ 16 , 17 ]. However, in most instances it is used to depict certain types of psychopathology or clinical interactions, and used on an ad hoc basis rather than as a standing curricular component associated with specific competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Human simulation has had a limited, but far from trivial role in psychiatric education and training[ 16 , 17 ]. However, in most instances it is used to depict certain types of psychopathology or clinical interactions, and used on an ad hoc basis rather than as a standing curricular component associated with specific competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, psychiatric education is ideally positioned to move from the prevailing use of standardized patients, to one in which actors, unencumbered by rigid scripts to adhere to, can be utilized as simulated patients instead. 21 Models such as CCPS that rely on actors' spontaneity can support reflective practice and innovative supervision by opening up a full range of realistic interactions with learners. Second, through their expertise in mental illnesses and the use of intersubjectivity as a means of understanding and healing, psychiatrists can advance the destigmatization of mental health conditions by sharing their own journeys.…”
Section: Discussionmentioning
confidence: 99%
“…19 The use of SPs in psychiatric education has been criticized as limited in its application and "most problematic for teaching psychotherapy and assessing complex interpersonal skills, such as empathic responsiveness". 20 However, a growing literature, as recently reviewed, 21 reveals that SP use can in fact be fruitfully applied as one potential remedy for the discipline's imaging woes. The unique strengths of SPs in psychiatry may in fact reside in the opportunity they provide to delve deeply into interpersonal complexity.…”
Section: Theory Applied: Enhancing Psychiatric Education Showing: Imaging Mental Illnesses and Psychiatric Practicementioning
confidence: 99%
“…Extensive research has demonstrated the benefits of incorporating clinical simulation into psychiatric/mental health nursing curricula, emphasizing increased confidence and critical thinking to address the abovementioned difficulties [ 18 ]. Significant changes have occurred over the past decade, with many recent experiments and meta-analyses strongly supporting simulation-based mental health education for healthcare professionals [ 27 ].…”
Section: Introductionmentioning
confidence: 99%